Mother Midwifery Care At Work With Asi Granting Exclusive In Pekanbaru City Maternity Hospital Cempedak: Mother Midwifery Care At Work With Asi Granting Exclusive In Pekanbaru City Maternity Hospital Cempedak - Yulrina Ardhiyanti (Institute Of Computer Science (IOCS), 2020)
Exclusive breast milk is breast milk given to infants since birth for six months, without adding or replacing with other foods or beverages. Many babies do not get Exclusive Breast Milk. One of the obstacles of exclusive breastfeeding is due to the reason the mother works. Often mothers experience some conflicts between breastfeeding and outside work. The purpose of this case study is to be Able to perform Midwifery care in the Working Mom with Exclusive Breastfeeding. The method used in the implementation of this case study with the Midwifery management approach is then documented in the form of SOAP. This case study was conducted in RB Cempedak then Followed by home visit for three visits. Evaluation of Midwifery care given to Ny's patient. D age of 20years with exclusive breastfeeding problems can be resolved within 3 days. Therefore, it is expected to service providers, especially RB Cempedak in order to improve Midwifery services, especially to health service providers in exclusive breastfeeding.